Experiments on Ant-Like Cooperative Robots - Lam, Yoke Khei (2004)
This thesis investigates the application of biologically inspired concepts, particularly ant foraging behaviour to cooperative robotics. In the esperiments, ant-inspired algorithm is realized on three real mobile robots with minimal intelligence that cooperate to complete forage task. These robots are developed with an obstacle detection system, a target detection system, a fast vision tracking system, an infrared communication and localization system and a radio frequency communication system.